The Role of Realistic Channel Geometry Representation in Hydrological Model Predictions. (10th June 2020) - Brackins, John; Moragoda, Nishani; Rahman, Azbina; Cohen, Sagy; Lowry, Christopher
Abstract: A key element in hydraulic and hydrologic modeling is the specification of representative channel geometry. For continental‐scale modeling, the large amount of high‐resolution data required, as well as the considerable computational effort needed to incorporate such data, has led to simplifying assumptions such as rectangular or trapezoidal channels for river reaches. The National Water Model (NWM) uses a trapezoidal channel representation for 2.7 million river reaches to forecast water discharge for the entire continental United States. This has created uncertainties in when to initiate hydraulic predictions. The aim of this study is to: (1) evaluate the impact of simplified (NWM trapezoidal) channel geometry representation on hydrological model predictions and (2) suggest an improved representation of channel geometry while maintaining parsimony in model input and runtime. The Hydrologic Engineering Center's River Analysis System model was used to simulate hydraulic dynamics in three study sites under varying streamflow conditions (including flooding) with four different geometry representations at each site: NWM (trapezoidal), surveyed, and two proposed generalized geometries. Statistical analyses show that more realistic channel geometry improves simulated Muskingum‐Cunge routing parameters and stage/discharge predictions, indicating potential for geometric improvements to enhance hydrological models like the NWM. Abstract : Research Impact Statement : Improved representations of channel geometry have potential to substantially improve simulation of continent‐wide hydrology, especially for flood forecasting.